The knowledge, perceptions, attitudes, and perceived risk in HIV/AIDS among women in Malaysia: a cross-sectional study - Tham, Jen Sern (Asian Economic and Social Society, 2018)
The remarkable challenge in alleviating HIV/AIDS rates in Malaysia continued from its first case in 1986. Since then, a number of government initiatives have been put in place to address the escalating rates of HIV/AIDS especially among people who inject the drug (PWID). While HIV infections among intravenous drug users reportedly saw a steady decline, we seem to be leaving some people behind—women. This study seeks to examine HIV/AIDS knowledge, perceptions, attitudes, and perceived risk among women in Malaysia. We recruited 384 respondents, including 170 males and 210 females. As this research focused on women, 210 females were therefore selected for data analysis. The results show that the knowledge of HIV/AIDS modes of transmission among the surveyed respondents were rather high. However, there were some respondents who still believed that kissing and sharing utensils are the modes of HIV/AIDS transmission. Most of the respondents had moderate positive perceptions and a discriminatory attitude towards people living with HIV/AIDS (PLHIV). In terms of respondents' perception of risk of HIV/AIDS infection, surveyed respondents did not perceive themselves to be at risk of HIV infection. Nevertheless, they would protect themselves or their partners from HIV/AIDS infection by using condoms. More open discussion about HIV/AIDS should be held not only to raise the level of awareness but also to promote healthier behaviour and eliminate stigma and discrimination towards PLHIV.